Certified Kubernetes Application Developer (CKAD), 2nd Edition - van Vugt, Sander (Pearson IT Certification, 2021)
Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing. Certified Kubernetes Application Developer (CKAD), 2nd Edition.